Tpr Deficiency Disrupts Erythroid Maturation With Impaired Chromatin Condensation in Zebrafish Embryogenesis - Wu, Shuang; Chen, Kai; Xu, Tao; Ma, Ke; Gao, Lei; Fu, Cong; Zhang, Wenjuan; Jing, Changbin; Ren, Chunguang; Deng, Min; Chen, Yi; Zhou, Yi; et al. (Frontiers in Cell and Developmental Biology, 2021)
Vertebrate erythropoiesis involves nuclear and chromatin condensation at the early stages of terminal differentiation, which is a unique process to distinguish mature erythrocytes from erythroblasts. However, the underlying mechanisms of chromatin condensation during erythrocyte maturation remain elusive. Here we reported a novel zebrafish mutantcas7 with erythroid maturation deficiency. Positional cloning showed that a single base mutation in tprb gene, which encodes nucleoporin translocated promoter region (Tpr), is responsible for the disrupted erythroid maturation and upregulation of erythroid genes, including ae1-globin and be1-globin. Further investigation revealed that deficient erythropoiesis in tprbcas7 mutant was independent on HIF signaling pathway. The proportion of euchromatin was significantly increased, whereas the percentage of heterochromatin was markedly decreased in tprbcas7 mutant. In addition, TPR knockdown in human K562 cells also disrupted erythroid differentiation and dramatically elevated the expression of globin genes, which suggests that the functions of TPR in erythropoiesis are highly conserved in vertebrates. Taken together, this study revealed that Tpr played vital roles in chromatin condensation and gene regulation during erythroid maturation in vertebrates.